Cancer incidence and mortality near the Baglan Bay petrochemical works, South Wales. Issue 4 (April 1995) - Sans, S; Elliott, P; Kleinschmidt, I; Shaddick, G; Pattenden, S; Walls, P; Grundy, C; Dolk, H
Abstract : OBJECTIVES–To study incidence and mortality of leukaemias, cancer of the larynx, and other cancers near the petrochemical plant at Baglan Bay, in response to local concerns of an alleged cluster of cancers in the vicinity. METHODS–This is a small area study of cancer incidence, 1974-84 and of mortality, 1981-91 based on the national postcoded data held by the Small Area Health Statistics Unit and with population and socioeconomic data from the 1981 census. The study is centred on BP Chemicals Ltd, Baglan Bay, Port Talbot, West Glamorgan, South Wales and includes a general population sample of 115, 721 people (1981 census) living within 7.5 km of the plant. Cancer incidence and mortality for all cancers, leukaemias, and cancer of the larynx were examined within 7.5 km and 3 km of the plant, and tests for decline in risk of these cancers with distance from the plant were carried out. Mortality from several other cancers possibly associated with the petrochemical industry was also studied. RESULTS–There were 5417 incident cancer cases and 2458 cancer deaths within 7.5 km of the plant during the periods of study. There was an 8% excess incidence of all cancers within 7.5 km, and a 24% excess of cancer of the larynx, consistent with a general excess of these cancers in West Glamorgan, but no apparent decline in incidence with distance from the plant, nor excess mortality. There was also no evidence of decline in leukaemia incidence or mortality with distance, at all ages or in children. Among the other causes included in the mortality study, there was an excess of multiple myeloma within 7.5 km, especially among women, and a significant decline in mortality from non-Hodgkin's lymphomas although there was no excess overall within 7.5 km. CONCLUSIONS–The apparent excess incidence of all cancers and cancer of the larynx within 7.5 km of the BP Chemical Ltd works was consistent with an excess more generally in West Glamorgan, possibly related, at least to some extent, to cancer registration in Wales. There was no excess mortality from these cancers. The results for multiple myeloma and especially non-Hodgkin's lymphomas may have been chance findings in view of the multiple tests of significance carried out in the study. A study of lymphatic and haematopoietic cancers near oil refineries in Great Britain is to be undertaken that will help put the findings of the present study in wider context.